Knowledge, Attitudes, and Behaviors of Students at Islamic Boarding School X toward COVID-19 Incidence in 2022 - Haninda, Aisyah Raisa; Susanna, Dewi; Kusuma, Aria; Fitria, Laila (Kesmas, 2022)
The spread of COVID-19 can occur in various settings but most notably in gathering places. Health protocols to avoid the spread of COVID-19 may be influenced by the knowledge and attitude of individuals. This study examined the relationship between knowledge, attitudes, and behaviors of students at the Islamic Boarding School X in Serang City, Banten Province, Indonesia, with the COVID-19 incidence. A quantitative approach with a cross-sectional study design was used. The study population consisted of 994 students, from which (via the Slovin’s formula) a minimum sample size of 285 students was obtained. Data collection was carried out using an online validated questionnaire. The data collected related to age, sex, education level, knowledge level, attitude, behavior, and the COVID-19 incidence as experienced by the respondents. The results showed that most students had low-level knowledge (71.9%), negative attitudes (51.3%), and poor behaviors (53.2%) regarding the COVID-19. Most of the students were infected by the COVID-19 (88%). Statistically, knowledge, attitude, and behavior had no significant relationship with the COVID-19 incidence (p-value>0.05). This study concludes that knowledge, attitude, and behavior are not related to the COVID-19 incidence.